Polysaccharide-based fast self-healing ion gel based on acylhydrazone and metal coordination bonds. (July 2020) - Zhu, Moshuqi; Jin, Hailun; Shao, Tan; Li, Yuyu; Liu, Jian; Gan, Lihui; Long, Minnan
Abstract: The development of environmentally friendly and durable gel materials based on biomass is becoming critical today. In this paper, a kind of self-healing ion gel based on acylhydrazone bonds was firstly prepared by eco-friendly polysaccharide materials. The gel can achieve rapid self-healing within minutes after cutting and has properties such as free-shapeable and adhesive properties, and it can also be used as a solid electrolyte in supercapacitors. On this basis, we introduced Fe3 O4 to the gel precursor and produced a kind of ion gel (OSA-PAM-Fe3 O4 -CNCs ion gel) which can realize self-healing instantly by combining acylhydrazone bond with metal coordination bond for the first time. Moreover, the strength of ion gel is more than 10 times than before. With the good Mechanical and electrochemical properties, the self-healing ion gels is expected to be used in the field of wearable flexible sensing. Graphical abstract: Unlabelled Image Highlights: The self-healing of prepared ion gel can realize instantly, much faster than reports. The combination of acylhydrazone bond and metal coordination bond is proved to be the mechanism. The self-healing gels are applied on supercapacitors as solid electrolytes and show good effects. The mechanical performance and self-healing time of gels were improved significantly by the aid of metal coordination bond.